Prevalence of pregnancy and postpartum hypertension in obese women living with HIV In Cape Town, South Africa - Phohlo, Nthabiseng (Department of Public Health and Family Medicine, 2025)
Background: In accordance with global hypertension practice guidelines, hypertension is defined as having systolic blood pressure ≥140 mm Hg and diastolic blood pressure ≥90 mm Hg in an office or clinic setting following repeated examination. Hypertension is one of the leading causes of morbidity and mortality in the world and it is a risk factor for many non-communicable diseases, particularly cardiovascular disease. In South Africa, management of hypertension remains suboptimal due to insufficient healthcare utilities. Roughly 8.22 million adult South Africans who do not have private insurance have hypertension and the direct healthcare costs associated with hypertension were projected to be around 10.1 billion. Consequently, proactive interventions need to be reinforced in order to combat this growing epidemic and factors associated with it need to be well defined. Coupled with escalating trends of obesity and high prevalence of HIV, hypertension poses more thread to South African health system. Globally, obesity has increased since 1975 to 2016 from 3% to 11% among men, from 6% to 15% among women and from less than 1% to 8% in children. Conversely in South Africa, prevalence of obesity in adult men and women was 9% and 27% in 2003. Additionally, about 21.7% of women of child bearing age are living with HIV. More research is therefore required in order to inform relevant stakeholders to incorporate effective measures that can control and prevent this disease. Methods: A retrospective cohort study that used secondary data from previous studies was carried out. This data was for pregnant WLHIV, who presented themselves at Gugulethu community health facility from 2013 to 2018. The data was merged for analysis of hypertensive disorders of pregnancy (HDP) in association with body mass Index (BMI) and antiretroviral therapy (ART) initiation time. Women who were included in the study were those who were on ART before pregnancy (preconception) and those who initiated ART during pregnancy (post conception). Other risk factors associated with PIH and PPH were also determined. Hypertension was classified according to American hypertension guidelines. Descriptive analysis of the whole sample included 1859 WLHIV, 752 WLHIV of these were included in the sub-analysis of PPH. Analytical analysis was done by multinomial ordinal proportional logistic regression because the outcome had four ordered levels (normal, high-normal, grade1 and grade2). This analysis was done using R programming version 4.2.2. Ethical statement: Ethics approval was obtained from Human Research Ethics committee, Faculty of Health Sciences, University of Cape Town. Informed consent for parent studies, where data was collected from was obtained from the participants. In this study, no informed consent from the participants was required as these were already obtained from the parent studies. Results: Overall PIH prevalence was 67.7 cases per 1000 population. Prevalence of PIH was 67.7 cases per 1000 population stratified by ART initiation timing (42% preconception and 58% post-conception) and 67.9 cases per 1000 population stratified by BMI (a proportion of obese women was 67%). Conversely, PIH prevalence in obese women was 43 cases per 1000 population in the overall sample. Association between PIH and ART initiation timing (preconception) was OR; 0.76, 95% CI; 0.59 to 0.97, with p-value of 0.03. Association between PIH and BMI in obese women was; OR; 3.49, 95% CI; 2.42 to 5.15, p-values; <0.001. Overall PPH prevalence was 155 cases per 1000 population. PPH prevalence was 155 cases per 1000 population stratified by ART initiation timing (44% preconception and 56% post-conception) and 158.6 cases per 1000 population stratified by BMI (a proportion of 64% was obese women). Overall PPH prevalence in obese women was 101 cases per 1000 population. ART initiation timing (preconception) and PPH association was (OR; 0.67, 95% CI; 0.47 to 0.95), p-value; 0.03. BMI and PPH association in obese women was; (OR; 2.41, 95% CI; 1.51 to 3.96), p-value; < 0.001. Obesity, old age (≥35) and late booking at antenatal clinic were risk factors that showed a positive association with hypertension, with ORs; 3.49, 2.21 and 1.56 respectively. Conclusions: There is significantly high prevalence of PIH and PPH in women living with HIV in Cape Town. Obesity is the major risk factor for PIH and PPH. ART initiation timing (preconception) was negatively associated with PIH and PPH. Effective measures to manage and prevent hypertension in pregnant WLHIV need to be implemented to prevent PIH and PPH. Pregnant WLHIV need to be monitored for hypertension, particularly those above 35 years and those who are obese. Early booking at antenatal care should be encouraged to facilitate early monitoring of PIH.